Clinics, prognosis and new therapeutic options in patients with mucosal melanoma: A retrospective analysis of 75 patients. Issue 1 (January 2017) - Schaefer, Tim; Satzger, Imke; Gutzmer, Ralf
Abstract : Abstract: Mucosal melanomas represent a rare entity with different risk factors and molecular features compared to cutaneous melanomas. They arise most commonly from mucosal surfaces in the head/neck region, the female genital tract (FGT) and the anorectal region. The aim of this study was to evaluate clinics, prognosis, and treatment options of patients with mucosal melanoma, in particular with regard to different primary sites. We retrospectively analyzed 75 patients with mucosal melanomas diagnosed in the years 1993 to 2015 in our department. The primary melanomas were located in the head/neck region (n = 32), the FGT (n = 24), and the anorectal region (n = 19). The median age of the patients was 66 years. At initial diagnosis the primary melanoma was not completely resectable in 11 (15%) patients, 18 (24%) patients had regional lymph node metastases, and 7 (9%) patients distant metastases. During follow-up, 22 (29%) patients suffered from a local recurrence, in particular patients with primary melanoma in the head/neck region without postoperative radiotherapy. By multivariate analysis location of the primary melanoma in the head/neck area or anorectal region and presence of metastases at time of diagnosis represented poor prognostic factors for recurrence-free survival. In 62 tested individuals 7 KIT mutations were found, 2 BRAF mutations in 57 tested patients. Four patients received targeted therapies, 14 checkpoint inhibitors, 4 (1/1 on vemurafenib, 1/7 on ipilimumab, and 2/7 on PD-1 inhibitors) patients showed responses of more than 100 days duration. Mucosal melanomas are often locally advanced or metastatic at initial diagnosis, thus they require extensive staging procedures. The high rate of local recurrences in the head/neck region can be significantly reduced by postoperative radiotherapy. For the potential use of medical treatment a mutation analysis for KIT and BRAF genes should be performed. The use of new immunologic and targeted therapies has to be further evaluated.